Recruitments and Effectiveness of French Teachers: Determinants of Students’ Academic Achievement in French Language (British Journal of Multidisciplinary and Advanced Studies, 2025)
This study explores the impact of French teachers' recruitment and effectiveness on students' academic achievement in the learning of French language. The recruitment process includes qualifications, certifications, teacher-student ratios, and professional development. These play critical role in ensuring high-quality instruction. Teachers with higher levels of education with specialized language training and ongoing professional development are better equipped to foster effective language learning. Teacher effectiveness, which is shaped by pedagogical skills, classroom management and formative assessment practices, has a significant influence on students' language proficiency. Additionally, interactive and student-centered teaching methods, such as role-playing, group discussions, and multimedia tools, were found to improve student engagement and language proficiency. The study further examined the importance of teachers' language proficiency and the use of innovative teaching approaches; such as communicative language teaching and technology enhanced learning, in improving students’ French language acquisition. In addition, motivation, attitudes toward the language, and exposure to French language outside the classroom is very important. The research adopted a descriptive research design of a survey type, utilising questionnaires to gather data from students. The population for the study consisted of 50 French students and 10 French teachers using simple random sampling techniques from the schools that offer French. The findings highlighted the interconnectedness of teacher quality, student engagement, and external support in achieving academic success in the learning of French language and that both teacher-related factors and student motivation are critical to language acquisition and academic success in learning French. The study suggests ways to enhance the recruitment, effectiveness, and overall success of French language education. Based on these findings, the study recommended enhancing teacher training, adopting more interactive teaching methods, fostering student motivation, and providing opportunities for extracurricular learning to support students’ academic progress in French language education.